Contribution of liquid water content enhancing aqueous phase reaction forming ambient particulate nitrosamines - Choi, Na Rae; Park, Seungshik; Ju, Seoryeong; Lim, Yong Bin; Lee, Ji Yi; Kim, Eunhye; Kim, Soontae; Shin, Hye Jung; Kim, Yong Pyo (Environmental Pollution, 2022)
Contribution of liquid water content (LWC) to the levels of the carcinogenic particulate nitro(so) compounds and the chemistry affecting LWC were investigated based on the observation of seven nitrosamines and two nitramines in rural (Seosan) and urban (Seoul) area in South Korea during October 2019 and a model simulation. The concentrations of both the total nitrosamines and nitramines were higher in Seosan (12.48 ± 16.12 ng/m3 and 0.65 ± 0.71 ng/m3, respectively) than Seoul (7.41 ± 13.59 ng/m3 and 0.24 ± 0.15 ng/m3, respectively). The estimated LWC using a thermodynamic model in Seosan (12.92 ± 9.77 μg/m3) was higher than that in Seoul (6.20 ± 5.35 μg/m3) mainly due to higher relative humidity (75 ± 9% (Seosan); 62 ± 10% (Seoul)) and higher concentrations of free ammonia (0.13 ± 0.09 μmol/m3 (Seosan); 0.08 ± 0.01 μmol/m3 (Seoul)) and total nitric acid (0.09 ± 0.07 μmol/m3 (Seosan); 0.04 ± 0.02 μmol/m3 (Seoul)) in Seosan while neither fog nor rain occurred during the sampling period. The relatively high concentrations of the particulate nitrosamines (>30 ng/m3) only observed probably due to the higher LWC (>10 μg/m3) in Seosan. It implies that aqueous phase reactions involving NO2 and/or uptake from the gas phase enhanced by LWC could be promoted in Seosan. Strong correlation between the concentrations of nitrosodi-methylamine (NDMA), an example of nitrosamines, simulated by a kinetic box model including the aqueous phase reactions and the measured concentration of NDMA in Seosan (R = 0.77; 0.37 (Seoul)) indicates that the aqueous phase reactions dominantly enhanced the NDMA concentrations in Seosan. On the other hand, it is estimated that the formation of nitrosamines by aqueous phase reaction was not significant due to the relatively lower LWC in Seoul compared to that in Seosan. Furthermore, it is presumed that nitramines are mostly emitted from the primary emission sources. This study implies that the concentration of the particulate nitrosamines can be promoted by aqueous phase reaction enhanced by LWC.
Keywords: Ambients; Aqueous phase reactions; Atmospheric reactions; Carcinogenics; Free ammonia; Liquid water content; Nitramines; Particulates; Seosan; Seoul; Dust; Nitrosamines; Republic of Korea; Seoul; Water; Atmospheric reaction; Free ammonia; Liquid water content; Nitramines; Nitrosamines; Seosan; Seoul